Analysis of Gearbox Ratio Mismatchwith Main Engine RPM, Resulting in High Temperature Lubricating Oil Lubrication in the Gearbox of MV. Prakarsa Mas - Riswanto, Adi; Saktiono, Maxima Ari; Awwalin, Rodlitul (Universitas Hang Tuah, 2026)
Gearbox is a vital component in the ship propulsion system that functions to transmit power from the main engine to the propeller. On the MV. Mas Initiative, found a discrepancy between the gearbox rotation ratio with the RPM of the main engine, which has an impact on increasing the lubrication temperature of the gearbox lubricating oil to exceed the optimal limit. This condition can reduce lubrication efficiency, accelerate component wear, andreduce overall ship performance. This study aims to analyze the factors that cause gearbox ratio mismatch, evaluate its impact on lubricant temperature, and develop technical recommendations to overcome these problems. The method used is descriptive qualitative approach through direct observation, interviews with the crew, and literature studies. The results showed that the main causes of this discrepancy include damage to gearbox components, a non-optimal lubrication system, as well as a lack of regular maintenance. The high temperature of the lubricant has an impact on decreasing the viscosity of the oil and decreasing the efficiency of power transmission. Recommended solutions include regular cleaning of the oil cooler and filter, checking the pressure of the oil pump, as well as regular oil quality testing. It is expectedthat the results of this study canbe a referencein gearbox maintenance to improve the reliability and operational efficiency of the ship.